Penguatan Nilai-Nilai Karakter Siswa Melalui Manajemen Ekstrakurikuler Seni Islami di SMK Bina Madina Denpasar Tahun Pelajaran 2019/2020 - Ismail, Syarof Nursyah; Milhaq, M.; Qosim, Ahmad (STAI Denpasar Bali, 2022)
In every educational institution, management is needed that prioritizes student character education, this management can be carried out outside school hours. Similarly, at Bina Madina Denpasar Vocational School, practicing Islamic arts curricular management extracts which aim to strengthen students' character values. The aim of this research is to find out: 1) The implementation of strengthening students' character values ​​through Islamic arts extracurricular management at Bina Madina Denpasar Vocational School for the 2019/2020 academic year, 2) What are the supporting and inhibiting factors for the implementation of strengthening students' character values ​​through extracurricular management Islamic art at Bina Madina Denpasar Vocational School for the 2019/2020 academic year. This research uses a descriptive qualitative approach. The resource persons in this research were the school principal, head of curriculum, head of student affairs, religious teachers, and students. The data collection techniques used were interviews, observation and documentation. Data analysis was carried out interactively, starting from data reduction, data presentation, and drawing conclusions. The research results found: 1) The implementation of strengthening students' character values ​​was carried out by practicing recitation, discussions among members, advice/advice. Conceptualized in three pillars; The Moral of Knowing, the Moral of Loving, and the Moral of Doing. 2) Supporting factors for strengthening students' character values ​​are the active role of educators and support from the school principal, as well as adequate infrastructure. 2) The inhibiting factors are that students are not consistent in implementing noble morals, students' abilities are limited, time is not right, and the distance between the school and the students' home is quite far.